(untitled) (Filološke pripombe, 2020)
The paper describes the unusual and traumatic history of Žarko Radaković and his emergence as a writer. Having been in emigration since the late 1970s, Radaković turned to the strategy of “productive reception”, which enabled him to use the opus of two great artists (the writer Peter Handke and the artist Julije Knifer) as a springboard for his own work. Regarding them as his poetic fathers, Radaković conceived his work as a following in the footsteps of his fathers.